Determinan Pengambilan Keputusan Berwirausaha pada Mahasiswa Akuntansi STIE Surakarta - Oktavia Dwi Kusumaningrum; Ismunawan Ismunawan (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to determine whether there is an influence of e-commerce, social media, accounting information systems, and business capital on entrepreneurial decision making. The population used in this research were 6th semester students majoring in accounting at the Surakarta Department with a sample of 105 respondents. The type of method used in this research uses quantitative methods. Data analysis uses multiple linear regression analysis using SPSS version 25. The research results show that the independent variables e-commerce, accounting information systems, and business capital have a positive or significant impact, while the results from the social media variable do not have a positive impact or not. significant impact on entrepreneurial decisions.